Inkling a short story compilation - Nur Fatin Afrina (WhiteCoat Group Sdn Bhd, 2021)
A creative compilation of short stories and poems by yours truly; A girl sins and expects thunder to strike her. A doctor prescribes daily dose of " I love you " to cure Alzheimer's. A student drives in the middle of the road with intentions to be hit.